Combined delivery of VEGF and IGF-1 promotes functional innervation in mice and improves muscle transplantation in rabbits. (September 2019) - Raimondo, Theresa M.; Li, Hehuan; Kwee, Brian J.; Kinsley, Sarah; Budina, Erica; Anderson, Erin M.; Doherty, Edward J.; Talbot, Simon G.; Mooney, David J.
Abstract: Microvascular muscle transfer is the gold standard for reanimation following chronic facial nerve paralysis, however, despite the regenerative capacity of peripheral motor axons, poor reinnervation often results in sub-optimal function. We hypothesized that injection of alginate hydrogels releasing growth factors directly into donor tissue would promote reinnervation, muscle regeneration, and function. A murine model of sciatic nerve ligation and neurorrhaphy was first used to assess the ability of gel delivery of vascular endothelial growth factor (VEGF) and insulin-like growth factor-1 (IGF-1) to promote functional reinnervation. VEGF + IGF-1 gel delivery to aged mice resulted in prolonged ability to control toe movement, increased toe spreading, and improved static sciatic index score, indicative of improved sciatic nerve and neuromuscular junction function. Further, a 26% increase in muscle fiber area, and 2.8 and 3.0-fold increases in muscle contraction force and velocity, respectively, were found compared to blank alginate in the murine model. This strategy was subsequently tested in a rabbit model of craniofacial gracilis muscle transplantation. Electromyography demonstrated a 71% increase in compound muscle action potential 9 weeks after transplantation following treatment with VEGF + IGF-1 alginate, compared to blank alginate in the rabbit model. Improving functional innervation in transplanted muscle via a hydrogel source of growth factors may enhance the therapeutic outcomes of facial palsy treatments and, more broadly, muscle transplantations.